Desain Karakter dalam Buku Cerita Bergambar Giri Gajah - Nuria Lathifatul Qolbi; Aris Sutejo; Restu Ismoyo Aji (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
The richness of local legends, such as the legend of Giri Gajah from Gresik, faces the risk of being forgotten due to a lack of visual elements appealing to child audiences, especially those aged 8-10 years old. To revitalize this legend, a picture storybook was designed by creating character designs that could captivate children aged 8-10. This dynamic educational medium is the primary target. The focus of the design lies in the character design, making it the core visual element and narrative driver, which connects the oral tradition with the needs of contemporary media. The research method used is design thinking. The design results established four main characters, namely Pandu, Sunan Giri, Sunan Giri's Grandchild, and Gajah (Elephant), using a Semi-Realistic Cartoonist illustration style. This style was chosen for its ability to bridge the reality of local culture with a cheerful visual appeal. This design successfully created an effective medium for the preservation of local culture and the improvement of children's interest in reading.